Application of wheat straw autohydrolysis liquor to xylanase and β-xylosidase large-scale production in a stirred tank bioreactor - Michelin, Michele (2009)
Research into microbial xylanases production has increased due to its several applications. In this context, studies that make this practice feasible are important. Wheat bran is an inexpensive byproduct, which contains around 28% hemicellulose; however, the wheat bran particles suspended in the cultivation medium have to be decomposed to soluble compounds to be used by the fungi and the treatment of lignocellulosic materials in autohydrolysis processes makes this easier. The inclusion of these treated materials in the nutrient media can be a strategy to increase and undervalue xylanase production. The best conditions for xylanase and β-xylosidase production were observed when A. ochraceus was cultivated with 1% wheat bran added 10% wheat straw autohydrolysis liquor as carbon source, this substrate was more favorable when compared with xylan, wheat bran and wheat straw autohydrolysis liquor used separately. The application of this substrate in a stirred tank bioreactor shows the need for improvements of the fermentation process.